Nursing values as social practice: a qualitative meta-synthesis - Zoboli, Elma Lourdes Campos Pavone (2013)
OBJECTIVE: to identify values which structure and guide nursing as social practice. METHOD: qualitative meta-synthesis. RESULTS: three concepts were identified: The tension between technique, organization and ethics in the nurse's practice; Historical carry-overs of the values which run through nursing practice; Attention to ethics, to reform of the health system, and to the humanization of care. These led to the synthesis of the principal variables 'planning' and 'care', which represent, respectively, guiding values of the technical-operative and ethical-moral elements of the social practice of nursing. CONCLUSION: these values are articulated through the prism of ordering so as to care well. Their recognition contributed to a better understanding of the process of health care and nursing care.